Effectiveness of Chitosan and Ag-Nanoparticle Films on the Quality of Chicken Meat - Ahmed Alkhashb; Thamer Alhaji; Karkaz Thalij (Mesopotamia Journal of Agriculture)
AbstractThis study aims to evaluate the effectiveness of the composite films of chitosan (Ch) and silver nanoparticles (AgNPs) biosynthesized by the Aspergillus niger on the chemical qualities and microbial content of chicken breasts meat during storage at 4°C for 28 days. Over storage time pH, moisture content, and peroxide number of chicken breast meat were analyzed. The results indicated that the films of Ch alone or Ch-AgNPs had increased the values of all parameters the preservation periods. Regarding the microbial content, total bacterial count was decreased in both Ch and Ag-NPs over time cpared to the control. While lowest level was found in Ch-AgNPs samples These findings demonstrated that the meat samples coated with either Ch or Ch-AgNPs performed better than those without coating the during storage time. The Ch-AgNPs film became thicker after AgNPs were added. The chicken breast sample coated with Ch-AgNPs preserved the moisture content, pH values, peroxide number, percentage of F.F.A and bacterial counts better compared to the Ch sample and compared after 28 days of preservation, the values were %75.91, 6.9, 0.42 (mgO2/100g), %0.95, 5.08 (log10 cfu/g) respectively, which caused prolongation of the shelf life of the Ch-AgNPs sample.